Evangelistic belief and behavior among Canadian congregants. (December 2022) - Thiessen, Joel; Quantz, Kennedy; Wong, Arch Chee Keen; Walker, Keith; McAlpine, Bill
With the recent surge of "religious nones" in many Western nations, there is a growing interest among some church attenders to effectively "reach" this demographic. In this article, we build on theories of strictness and social embeddedness to tackle three questions regarding evangelistic belief and behavior in Canadian Catholic, mainline Protestant, and conservative Protestant congregations. First, in what ways are evangelistic beliefs and behaviors similar or dissimilar across theological traditions, notably when comparing stricter and less strict contexts? Second, how are evangelistic behaviors similar or dissimilar based on a person's frequency of church attendance? Third, what challenges do people confront in their evangelistic efforts? Drawing on survey data with over 9100 Catholic, mainline, and conservative Protestant respondents in over 250 Canadian congregations, this study compares responses across theological sectors, reported levels of importance that church members attach to evangelism, as well as church attendance frequency. Data reveal that those in religious traditions with stricter "insider–outsider" boundaries and who were more socially embedded in their religious groups (i.e., conservative Protestant traditions) were the most likely to embrace evangelistic attitudes and behaviors, in contrast to those in religious groups with less strict boundaries or social embeddedness in their religious group (i.e., United Church of Canada). However, those with the strongest "us–them" boundaries also found those boundaries particularly prohibitive to their evangelistic efforts reflected, in part, in a widespread leaning toward passive versus assertive forms of evangelism.